Teaching for creativity in the common core classroom - Beghetto, Ronald A. 1969-; Kaufman, James C.; Baer, John (Teachers College Press, 2015)
Creativity and the Common Core State Standards are both important to today?s teachers. Yet, for many educators, nurturing students? creativity seems to conflict with ensuring that they learn specific skills and content. In this book, the authors outline ways to adapt existing lessons and mandated curricula to encourage the development of student creativity alongside more traditional academic skills. Based on cutting-edge psychological research on creativity, the text debunks common misconceptions about creativity and describes how learning environments can support both creativity and the Common Core, offers creative lessons and insights for teaching English language arts and mathematics, and includes assessments for creativity and Common Core learning. Featuring numerous classroom examples, this practical resource will empower teachers to think of the Common Core and creativity as encompassing complementary, rather than mutually exclusive, goals.